INDEPENDENT OBJECTS AND THE SPECIFICS OF THEIR INTERACTIONS: ONTOLOGICAL APPROACH - Kharchenko, Yu. V. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
Abstract. It is described that world shows the diversity in terms of interlacing of multiple integrated systems. The whole universe in its ontical and ontological meaning, and social reality in which the whole public relations are concentrated and spiritual plane, reflecting, beyond possible and conceivable, facets of interaction are introduced. It is shown that we can trace and establish cause-and-effect relationships, analyzing the spatio-temporal characteristics of material objects only to some extent. And it is extremely difficult to find the same independent objects in its pure form or to fix the complete absence of interaction between them. As the result one can talk about some peculiarities of interaction by increases or decreases the level of interaction with the view of strengthening or weakening ties. Objects can be fully or partly independent, but relations between them still remain. In this investigation the author carries out the conceptualization of the phenomenon of independent objects and their interactions. It is confirmed that in nature and society principles of formation and deformation of the links are different. In fundamental sciences, which study the world as an infinite Universe, the terms "dependent variable" and "independent variable" are typically used in experimental investigations where we have to manipulate with some variables. In this sense, the "independence" of a variable is defined as independence of reactions, properties, intentions of the objects of the experiment. Some variables are assumed to be "dependent" on the actions of the object of the experiment or the conditions of the experiment. These variables, perhaps in implicit form, contain some information about the behavior or reactions of the object during the experiment. The key tasks are: to identify relationships between independent objects; to fix measure of their independence; to compare them with those mathematical models that represent the connections between the "dependent variable" and "independent variables". Based on ontological and phenomenological approaches, as well as the use of quantitative and probabilistic methods, the author carries out a comparative analysis of the phenomenon of independent objects in mathematical theory and in the social space.